الإجراءات العالمية من أجل المراعي المستدامة والرعي لتحقيق تحييد تدهور الأراضي - Louhaichi, Mounir; Masumbuko, Bora; Niamir-Fuller, Maryam; Herrera, Pedro; Liniger, Hanspeter; Mekdaschi-Studer, Rima; Bendandi, Barbara Bendandi; Turin, Cecilia; Magero, Chris; Chavez, Eric; Haddad, Fidaa; Badripour, Hossein; et al. (International Year of Rangelands and Pastoralists, 2024)
The Policy Brief (Arabic) by the IYRP Rangelands & Land Degradation Neutrality Working Group highlights the crucial role of rangelands, which cover over half of the Earth's surface, in achieving Land Degradation Neutrality (LDN) and advancing global goals such as the Sustainable Development Goals (SDGs). Despite their importance, rangelands and pastoralist communities face threats from uncontrolled land conversion, poor governance, and underinvestment. The brief calls for stronger global commitments to stop rangeland degradation, promote sustainable pastoralism, and set specific LDN targets for rangelands. It proposes eight key actions, including halting indiscriminate land conversion, recognizing the importance of pastoral mobility, strengthening governance, and increasing financial support for rangeland projects. By adopting these recommendations, the UNCCD Conference of the Parties (COP) can play a vital role in preserving rangelands, enhancing climate resilience, conserving biodiversity, and supporting pastoralist livelihoods